A Maui Babe: 24"x36" Acrylic on Canvas, 2025 - Gutierrez, Veronica (Northridge Review, 2025)
I have loved rainbow Eucalyptus Trees ever since I first laid eyes on them in Maui, Hawaii. I love how they look so different from everything around them that when I show pictures of them, people think they are made-up trees. While in Maui, I also witnessed the sexualization of Hawaiian women and the "Maui Babe". When traveling through the Maui rainforest down the road to Hana, I witnessed a real Maui babe, the land. I have chosen to depict these trees because the nature of the island is the true beauty of Maui, not the sexualization of women.